COVID-19's Impact on Mental Health - The Hour of Computational Aid? - Schuller, Bjorn W.; Löchner, Johanna; Qian, Kun; Hu, Bin (IEEE Transactions on Computational Social Systems, 2022)
Welcome to the fourth issue of IEEE Transactions on Computational Social Systems (TCSS) in 2022. First, we have some exciting news to share. In late June, Clarivate updated the Impact Factor of all journals which are indexed by Web of Science. According to the Journal Citation Reports, the 2021 Journal Impact Factor of IEEE TCSS was 4.727. Many thanks to all for your great effort and support.
CRIS-Team Scopus Importer:2024-11-26